2019
DOI: 10.1089/chi.2018.0044
|View full text |Cite
|
Sign up to set email alerts
|

Do Neighborhoods Matter? A Systematic Review of Modifiable Risk Factors for Obesity among Low Socio-Economic Status Black and Hispanic Children

Abstract: Background: Childhood obesity increases the risk of obesity and harmful comorbidities later in life. It is influenced by characteristics of a child's neighborhood, particularly among underserved groups. Our objective was to systematically review the evidence relating neighborhood environment and obesity risk among urban, low socioeconomic status (SES) Black and Hispanic children. Methods: We included studies published from 1993 through early 2017 from PubMed, SCOPUS, Web of Science, and Sociological Abstracts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 54 publications
1
27
0
Order By: Relevance
“…Poverty is a key neighborhood characteristic that has recently received increased attention in efforts to establish the relationship between neighborhood and obesity [24,[34][35][36]. Neighborhood poverty may impact obesity via two potential pathways [37].…”
Section: Introductionmentioning
confidence: 99%
“…Poverty is a key neighborhood characteristic that has recently received increased attention in efforts to establish the relationship between neighborhood and obesity [24,[34][35][36]. Neighborhood poverty may impact obesity via two potential pathways [37].…”
Section: Introductionmentioning
confidence: 99%
“…Children with no place to go or no one to play with are less likely to engage in running, jumping, and performing large motor skills (Fegert et al, 2020). A recent systematic review suggests that body mass index may be related to living in a lower-income community ( Johnson et al, 2019 ). Data from two international studies found that better macro-economic indicators were related to lower rates of childhood obesity ( Olaya et al, 2015 ), and distance to green space was the most significant factor contributing to obesity in urban children (Manandhar et al, 2019).…”
mentioning
confidence: 99%
“…These statistics are concerning given that low physical activity in youth is associated with childhood obesity and other health conditions (e.g. diabetes, cardiovascular disease) and contributes to unhealthy lifestyles in adulthood ( Johnson et al, 2019 , Masoumi, 2017 , Rhodes et al, 2018 , Hallal et al, 2006 ). Ecological models of physical activity posit that factors across multiple levels, such as individual, psychosocial, environmental, and policy levels influence physical activity behaviors ( Molina-García et al, 2017 , Perez et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%